Stattic V, a STAT3 inhibitor, affects human spermatozoa through regulation of mitochondrial activity. Issue 4 (20th December 2012) - Lachance, Catherine; Goupil, Serge; Leclerc, Pierre
Abstract We have recently shown that many mediators of the JAK/STAT signaling pathway are present in ejaculated human spermatozoa. Among them, STAT3 is detected mainly in membranes and flagellar cytoskeletal fractions. In order to determine the importance of STAT3‐mediated signaling, sperm were incubated with Stattic V, a specific inhibitor. Effects on motility were evaluated by CASA, sperm acrosomal integrity was evaluated by FITC conjugated lectin (PSA or PNA) staining, and protein phosphotyrosine content was assessed by Western blot using a monoclonal anti‐phosphotyrosine antibody. INDO1‐AM and JC‐1 were used to measure sperm intracellular calcium and mitochondrial membrane potential, respectively, by flow cytometry, and reactive oxygen species (ROS) production was investigated by luminol‐based assay. Percentages of motility and motility parameters were significantly affected by Stattic V. This later also significantly increased intracellular Ca2+ levels, progesterone‐ and calcium ionophore (A23187)‐induced acrosome reaction. On the other hand, a significant decrease in ATP content was measured when sperm were treated with Stattic V, associated with depolarization of mitochondrial membrane and elevated ROS production. These results suggest that STAT3 is involved in sperm functions, at least through regulation of mitochondrial activity. This further emphasizes that STAT3 mediates cellular activities in a manner different than strictly the activation of gene transcription. J. Cell. Physiol. 228: 704–713, 2013. © 2012 Wiley Periodicals, Inc.